R&D, Innovation and Productivity: The Role of Public Support - Elnasri Amani; Kevin J. Fox (KDI Journal of Economic Policy, 2015)
Research and innovation are widely agreed to be major driving forces behind long-term productivity and economic growth. However, the relationships have proven to be difficult to quantify. We make reference to the international literature and draw on recent research for Australia to advance our understanding of these relationships. Particular focus is on assessing the impact of publically financed R&D on productivity. The conclusions have implications for government innovation policies, providing insight into possible productivity gains from funding reallocations. Specifically, the findings suggest that government research agencies and higher education are areas in which investment leads to more potential productivity gains.
Keywords: C36; O31; O33; O38; 330; Research and Development; Productivity; Innovation; Intangible asset; Public funding